PEDAGOGICAL OPPORTUNITIES OF USING REFLECTIVE APPROACH ON THE DEVELOPMENT OF CULTURAL VIEWS OF FUTURE TEACHERS - Kholbotaeva Dilfuza Usmon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
This article focuses on the pedagogical aspects of using a reflexive approach in the developing cultural worldviews of future teachers, the importance of cultural models, cultural knowledge, critical analytical thinking in the developing cultural worldviews of future teachers. This article serves as a resource for the scientific and pedagogical community, teachers, future teachers, researchers.